(3ebOeI aj GdJLhjOs - (3CHh GdCUHZ YHO GdYRjR Hf Ydj Hf eMeO Hf YHO GdYRjR Hf GdWMGf GdETHjdj, GHf GdWMGf,J (B560 (3g` s
(3ChdgG (B:s
(3aCQHYI CbUi GddSGf hhSWg hWQag hMGaJg s
(3BNQgG (B:s
(3heMjGi heeGJi hLfJiq s
(3Vef eLehY , JQJjHgG (B: 4s
(3JUhjQ GdejcQhajde aj ZGjI GdShAs
(3QGLY eYdheGJ GdQSGFd bHdgG HPGJ GdeLehYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B147s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3GdbQGAGJ hGdJLhjOs